Design and Application of Air/Sewage Source Heat Pump System - Hu Peng; Wang Tiejun; Li Jiping; Xu Wei; Xia Xingxiang (Zhileng xuebao)
In order to achieve energy conservation and emissions reductions, an air source/sewage source heat pump hot water system was designed. Field tests were conducted in a demonstration project on Tunxi Road at Hefei University of Technology. The results show that at an ambient temperature of 8 ± 1.2 ℃ and a water supply temperature of 50 ℃ condition, the wastewater temperature is decreased from 30.6 ℃ to 15.5 ℃ through preheater and waste heat recovery. Heat recovery energy accounts for about 1/3 of the total energy for hot water heating. At an ambient temperature of 10 ± 1 ℃ and a water supply temperature of 45 ℃ condition, the energy efficiency of the composite heat pump system was 3.45. Compared with a separate air source heat pump, the energy efficiency is increased by 18%. Compared with a gas water heater and an electric water heater, the composite heat pump system can reduce operating costs by 53.3 and 72.4%, respectively. The results show obvious advantages of composite heat pump system on energy saving, environmental protection, and cost reduction.